Safety and efficacy of changing to the travoprost/timolol maleate fixed combination (DuoTrav) from prior mono- or adjunctive therapy - Norbert Pfeiffer (Dove Medical Press, 2010)
Norbert Pfeiffer1, Maria-Luise Scherzer2, Hubert Maier3, Sonja Schoelzel4, Mark C Jasek5, Jeanette A Stewart6, William C Stewart6 On behalf of the DuoTravMED study group1Johannes Gutenberg-Universität Mainz, Mainz, Germany; 2Regenstauf, Germany; 3Gerolzhofen, Germany; 4Institutes of Molecular Medicine, University of Freiburg, Department of Surgery, Freiburg, Germany; 5Alcon Laboratories, Inc., Fort Worth, TX, USA; 6PRN Pharmaceutical Research Network, LLC, Charleston, SC, USAPurpose: To assess the safety and efficacy of changing to the travoprost/timolol fixed combination (TTFC) from other mono- or adjunctive therapies.Patients and methods: A prospective, open-label, observational cohort of primary open-angle glaucoma and ocular hypertensive patients whose intraocular pressure (IOP) was uncontrolled on prior therapy or was not on target. Patients were changed from prior mono- or adjunctive treatment at Day 0 to TTFC dosed every evening and underwent active treatment efficacy and safety evaluations at Week 12.Results: In 474/522 (91%) patients who completed this trial an IOP (mm Hg) of 21.9 ± 2.0 on prior treatment was reduced by TTFC at Month 3: from all prior treatments 5.6 ± 2.6; from monotherapy 5.9 ± 2.3; from adjunctive treatments 4.5 ± 2.9; and from several of the most frequent individual treatments: timolol 5.7 ± 2.2; latanoprost 6.3 ± 2.6; and latanoprost/timolol fixed combination 4.4 ± 1.9. Ocular hyperemia was the most frequent adverse effect (n = 21, 4%). Both patients and physicians preferred TTFC compared to all prior and common individual treatments. The solicited symptom survey showed, following a modified Bonferroni correction (α/5), a reduced incidence with TTFC of ocular pain (P = 0.01) while the prior medicine had a lower incidence of burning on instillation (P < 0.001).Conclusions: Changing patients from prior mono- or adjunctive therapy to TTFC can provide on average a further reduction in IOP while demonstrating a favorable safety profile and a high patient preference.Keywords: travoprost/timolol fixed combination, primary open-angle glaucoma, ocular hypertension, safety, efficacy, intraocular pressure